NEDD4L-induced ubiquitination mediating UBE2T degradation inhibits progression of lung adenocarcinoma via PI3K-AKT signaling - Yongbing Chen (BMC, 2021)
Abstract Background A number of studies have indicated that Ubiquitin-conjugating enzyme E2T (UBE2T), as an oncogene, promotes progression and metastasis of lung cancer, including lung adenocarcinoma (LUAD), but it is completely unknown whether and how UBE2T is ubiquitylated and degraded, and by which E3 ligase. NEDD4L plays a critical role in the regulation of cellular processes of various cancers, most of which is attributed to its E3 ubiquitin ligase function. However, the relationship between NEDD4L and UBE2T in LUAD has not been elucidated. Methods The relationship between NEDD4L and UBE2T in LUAD tissues and cells was found by bioinformatic analyses and immunoblotting. Cell counting kit-8, colony formation assay, half-life analysis and the in vivo ubiquitylation assay, generation of xenograft model were performed to determine how NEDD4L regulates UBE2T and its downstream signaling pathway in vitro and in vivo. Results Bioinformatic analyses found that NEDD4L, as a potential correlation E3 ligase of UBE2T, was negatively correlated with UBE2T in LUAD. Consistently, UBE2T protein half-life was shortened or extended by NEDD4L overexpression or depletion, respectively. NEDD4L inhibited LUAD cell progression in vitro and in vivo via inducing the ubiquitination-mediated UBE2T degradation, which repressed PI3K-AKT signaling. Similarly, NEDD4L predicted a better patient survival, whereas UBE2T predicted a worse survival. Conclusions Collectively, our results reveal that NEDD4L is a novel E3 ligase of UBE2T, which can inhibit PI3K-AKT signaling by targeting for UBE2T ubiquitination and degradation, resulting in repression of LUAD cell progression.